Protective Effects of N-Acetyl-L-Cysteine in Human Oligodendrocyte Progenitor Cells and Restoration of Motor Function in Neonatal Rats with Hypoxic-Ischemic Encephalopathy. (31st March 2015) - Park, Dongsun; Shin, Kyungha; Choi, Ehn-Kyoung; Choi, Youngjin; Jang, Ja-Young; Kim, Jihyun; Jeong, Heon-Sang; Lee, Wooryoung; Lee, Yoon-Bok; Kim, Seung Up; Joo, Seong Soo; Kim, Yun-Bae
Abstract : Objective . Since oligodendrocyte progenitor cells (OPCs) are the target cells of neonatal hypoxic-ischemic encephalopathy (HIE), the present study was aimed at investigating the protective effects of N -acetyl-l -cysteine (NAC), a well-known antioxidant and precursor of glutathione, in OPCs as well as in neonatal rats. Methods . In in vitro study, protective effects of NAC on KCN cytotoxicity in F3.Olig2 OPCs were investigated via MTT assay and apoptotic signal analysis. In in vivo study, NAC was administered to rats with HIE induced by hypoxia-ischemia surgery at postnatal day 7, and their motor functions and white matter demyelination were analyzed. Results . NAC decreased KCN cytotoxicity in F3.Olig2 cells and especially suppressed apoptosis by regulating Bcl2 and p-ERK. Administration of NAC recovered motor functions such as the using ratio of forelimb contralateral to the injured brain, locomotor activity, and rotarod performance of neonatal HIE animals. It was also confirmed that NAC attenuated demyelination in the corpus callosum, a white matter region vulnerable to HIE. Conclusion . The results indicate that NAC exerts neuroprotective effects in vitro and in vivo by preserving OPCs, via regulation of antiapoptotic signaling, and that F3.Olig2 human OPCs could be a good tool for screening of candidates for demyelinating diseases.